Diagnostic criteria and management of metabolic syndrome: Evolution overtime (2020)
The beginnings of the Metabolic Syndrome (MetS) as a suspected, not yet recognized entity can be traced back to 1923 when a study concerning a particularly common clustering of metabolic entities observed in diabetic patients was first published. Years of research and endless debate yielded the currently accepted MetS definition and diagnostic criteria, even if some components and their cut-off points are still up for discussion. To date, MetS are defined as a clustering of metabolic risk factors that greatly increase the incidence of cardiovascular disease (CVD) and type 2 diabetes (T2D), while also being closely related to various potentially deadly comorbidities. Furthermore, since early detection and management of MetS have been shown to decrease the risk for CVD and T2D, current research has focused on unifying diagnostic criteria and proposing novel parameters to facilitate MetS identification, while also promoting a healthy lifestyle as a preventive measure. With a deeper understanding of MetS pathophysiology comes the broadening of therapeutic targets open for study, thus expanding and enhancing the treatment methods currently in use. This review aims to summarize the evolution of MetS as a concept, development of the diagnostic criteria, current management, and future directions.